Following Mexican Youth : A Short-Run Study of Time Use Decisions - Baron, Juan D.; Popova, Anna; Sanchez, Angelica (World Bank, Washington, DC, 2016)
This paper exploits data from a rotating panel that follows individuals for four quarters to shed light on the factors driving the time use decisions and restrictions faced by Mexican youth. The results of the analysis imply that: (i) once youth aged 15 to 18 years old leave school, it is very unlikely that they will return; (ii) being "neither in work nor in school" (Nini) is a highly persistent condition; and (iii) marriage (perhaps motivated by teen pregnancy) increases the probability of girls leaving school and raising children by themselves, which may in turn increase their future likelihood of being Ninis, as well as the probability of their children growing up to become Ninis, potentially creating an intergenerational transmission of Nininess. Similar results are found for other countries in the region (Brazil and Argentina).